Total Th1/Th2 cytokines profile from peripheral blood lymphocytes in normal pregnancy and preeclampsia syndrome - Iara dos Santos Fagundes; Eduardo Pletsch Brendler; Isadora Nunes Erthal; Raquel Jaqueline Eder Ribeiro; Rafaela Siviero Caron-Lienert; Denise Cantarelli Machado; Bartira Ercília Pinheiro da Costa; Carlos Eduardo Poli- (Taylor & Francis Group, 2022)
To evaluate total Th1/Th2 cytokines in CD3+ cells (immunocompetent T-lymphocytes) and peripheral blood lymphocytes, mostly CD4+ (T helper cells) and CD8+ (T-cytotoxic cells) subpopulations in preeclampsia. Total blood leukocytes and lymphocytes counts, percent cells: CD3+, INF-g+/CD3+, IL-4+/CD3+, and IL-10+/CD3+, CD4+/CD8+ were determined by flow-cytometry. Preeclampsia (n= 26) and normal pregnancy (n= 25) participants were age and gestational age matched. CD4+ lymphocytes count was higher in preeclampsia, compared with normal pregnancy (43.6 ± 5.8 vs 37.6 ± 5.6%; P< 0.001). CD3+ cells Th1/Th2 shift was not detected in preeclampsia, yet may be present in other cell types, such as CD4+ and CD3 - lymphocytes.